Impact of Spreading Rate and Age‐Offset on Oceanic Transform Fault Morphology. Issue 2 (24th January 2022) - Ren, Yu; Geersen, Jacob; Grevemeyer, Ingo
Abstract: Oceanic transform faults (OTFs) are an inherent part of seafloor spreading and plate tectonics, whereas the process controlling their morphology remains enigmatic. Here, we systematically quantify variations in transform morphology and their dependence on spreading rate and age‐offset, based on a compilation of shipborne bathymetric data from 94 OTFs at ultraslow‐ to intermediate‐spreading ridges. In general, the length, width and depth of OTFs scale systematically better with age‐offset rather than spreading rate. This observation supports recent geodynamic models proposing that cross‐transform extension scaling with age‐offset, is a key process of transform dynamics. On the global scale, OTFs with larger age‐offsets tend to have longer, wider, and deeper valleys. However, at small age‐offsets (<5 Myr), scatters in the depth and width of OTFs increase, indicating that small age‐offset OTFs with weak lithospheric strength are easily affected by secondary tectonic processes. Plain Language Summary: In the past 5 decades, studies on oceanic transform faults (OTFs) have revealed significant complexity in their morphology, which calls for detailed quantitative analysis to study the processes controlling the morphology of OTFs. Using the most complete and advanced compilation of bathymetric data from ultraslow‐ to intermediate‐spreading ridges, we parameterized the morphological characteristics of OTFs and extracted length, width and depth for each transform fault from the compiled bathymetric data. Moreover, correlations between these morphological parameters and related tectonic factors (e.g., spreading rate, age‐offset) were investigated in this study. We find that correlations between morphological features and spreading rate are rather weak. Comparison of correlations suggests that age‐offset scales better with the morphological parameters, along with scatters mostly at small age‐offsets, indicating small‐age‐offset OTFs are unstable due to their weak lithospheric strength. Our observation evidences extensional tectonics at OTFs. Key Points: We compiled multibeam bathymetric data of 94 oceanic transform faults (OTFs) to quantify their morphological characteristics Morphology of OTFs is dominated by age‐offset rather than spreading rate Transform valleys get systematically deeper and wider with increasing age‐offset, implying extensional tectonics at OTFs